基督教的末世论的本体论地位 (中国基督教研究（ISSN：3068-479X）, 2023)
Chapter V , The Question of an Eschatological Ontology, in The Logic of Promise in Moltmann’s Theology, Christopher Morse, Philadelphia Fortress Press, 1979.